Pengantar balaghah bahasa Melayu - Mohd. Zaki Abd. Rahman,Mohamad Husin,Che Radiah Mezah (Penerbit Universiti Putra Malaysia, 2019)
Introduction to Malay speech based on Arabic speech
Keywords: Fachkunde; Malay language; Arabic language